2015
DOI: 10.1016/j.otsr.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Bankart repair in contact versus non-contact athletes

Abstract: The recurrence rate of Bankart repair in the contact athletes was 2 times higher in the open group and 3 times higher in the arthroscopic group than in the non-contact athletes. Clinical outcome of arthroscopic Bankart repair was similar to that of open procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 18 publications
1
43
1
1
Order By: Relevance
“…One of the most worrying problems is the recurrence of the dislocation, which is inversely proportional to the increase in age, with directly proportional associated lesions and risk of complications. Shoulder instability is a recurrent condition in various sports, but with different incidences, especially with pathological and clinical-pathological characteristics, age and sport type specific 11,12 . In literature, practice of an "overhead" or a "forced overhead" sport was the only risk factor identified of not returning to the same sport at a level that was similar or better following surgery 1 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the most worrying problems is the recurrence of the dislocation, which is inversely proportional to the increase in age, with directly proportional associated lesions and risk of complications. Shoulder instability is a recurrent condition in various sports, but with different incidences, especially with pathological and clinical-pathological characteristics, age and sport type specific 11,12 . In literature, practice of an "overhead" or a "forced overhead" sport was the only risk factor identified of not returning to the same sport at a level that was similar or better following surgery 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Using these criteria, the authors reported an overall recurrence instability rate of 8.3% in collision athletes treated with arthroscopic Bankart repair. In a recent study, Yamamoto et al 38 reported a higher recurrence rate in contact athletes compared with noncontact athletes after Bankart repair. Furthermore, the recurrence rates were higher after arthroscopic repair compared with open Bankart repair.…”
Section: Discussionmentioning
confidence: 97%
“…Yamamoto et al 59 found a recurrence rate of 4% in non-contact athletes with an ABR. In contrast, in contact athletes, there was a recurrence rate of 14%.…”
Section: Discussionmentioning
confidence: 99%